2017
DOI: 10.1103/physreva.96.042331
|View full text |Cite
|
Sign up to set email alerts
|

Continuous-variable steering and incompatibility via state-channel duality

Abstract: The term Einstein-Podolsky-Rosen steering refers to a quantum correlation intermediate between entanglement and Bell nonlocality, which has been connected to another fundamental quantum property: measurement incompatibility. In the finite-dimensional case, efficient computational methods to quantify steerability have been developed. In the infinite-dimensional case, however, less theoretical tools are available. Here, we approach the problem of steerability in the continuous variable case via a notion of state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 58 publications
1
63
0
Order By: Relevance
“…Here we implicitly assume that f g jm ¹ , but one can show that the equality f g jm = holds if and only if all POVM elements of A and B are proportional to , in which case the pair is trivially compatible (see appendix E.3.1). The above feasible point immediately implies that = ( ) the set of all POVM pairs with n A and n B outcomes, respectively, in dimension d. To the best of our knowledge, this measure was first introduced in [21] and studied further in [7,33,40,48]. Recently, it was given an operational meaning through state discrimination tasks [13,49,50].…”
Section: Upper Boundmentioning
confidence: 99%
“…Here we implicitly assume that f g jm ¹ , but one can show that the equality f g jm = holds if and only if all POVM elements of A and B are proportional to , in which case the pair is trivially compatible (see appendix E.3.1). The above feasible point immediately implies that = ( ) the set of all POVM pairs with n A and n B outcomes, respectively, in dimension d. To the best of our knowledge, this measure was first introduced in [21] and studied further in [7,33,40,48]. Recently, it was given an operational meaning through state discrimination tasks [13,49,50].…”
Section: Upper Boundmentioning
confidence: 99%
“…Our strategy might also be used to study the quantification of steerability for multi-setting scenarios, in particular, for three-setting scenarios for which the joint measurability problem of three qubit observables has already been investigated 42,43 . Our method might also be used in continuous variable steering, temporal and channel steering, for which the steerability of the state assemblages or the instrument assemblages can be connected to the incompatibility problems of the quantum measurement assemblages 44,45 . Hence, the steerability of the quantum states or the quantum channels might also be studied based on the corresponding measurement incompatibility problems.…”
Section: Discussionmentioning
confidence: 99%
“…This property is at the basis of many quantum phenomena such as uncertainty relations [34], quantum contextuality [35][36][37], Bell nonlocality [38,39] and steering [40,41]. In particular, it has been shown that a state assemblage is unsteerable if and only if a collection of measurements, called steering equivalent observables measurement assemblage (SEO) is jointly measurable [42,43]. In this work, we provide an even stronger quantitative connection: (1) the SEO defines the equivalence classes of state assemblages and their transformations via local filtering, and (2) its incompatibility is the maximal steerability over a class.…”
Section: Introductionmentioning
confidence: 99%